Jens Schröter, Benjamin A. Edsall, and Joseph Verheyden, Eds. Jews and Christians – Parting Ways in the First Two Centuries CE? Reflections on the Gains and Losses of a Model - Marcus, Joel (Studies in Christian-Jewish Relations, 2022)
No abstract is available.